The effects of leaf removal and artificial shading on the composition of Chardonnay and Pinot noir grapes - Isabella Ghiglieno; Fulvio Mattivi; Gabriele Cola; Davide Trionfini; Daniele Perenzoni; Anna Simonetto; Gianni Gilioli; Leonardo Valenti (OENO One, 2020)
Aims: The aim of this study was to assess the effects of leaf removal and bunch shading on the analytical composition of Pinot noir and Chardonnay (Vitis vinifera L.) grapes suitable for making premium sparkling wine. Method and results: Total bunch defoliation (TD) and different treatments using shading nets (TD1L, TD2L and ND1L) were evaluated in comparison with a test with no defoliation and shading (ND) over three seasons in the southern part of Franciacorta, one of the most famous Italian sparkling wine regions. Micrometeorological variables, yield components, musts and grapes chemical composition were evaluated. Shading practices lead to a delay in ripening and they improve the acidic content of must, thus resulting in a potential improvement in the quality of juice suitable for producing sparkling wines. Furthermore, this particular type of vine canopy management leads to changes in the phenolic content of grapes. Conclusions: From the results obtained it was possible to underline the positive effect - delaying ripening, preserving acid concentration and reducing flavonol content - of shading on the composition of Pinot noir and Chardonnay grapes suitable for making premium sparkling wine. Significance of the study: This study shows the importance of shading, because it delays grape ripening and thereby preserves the acidic content of musts and, specifically, deals with the problem of early ripening related to the climate change now underway.